The influence of work motivation on employee performance at the Indonesian Red Cross blood transfusion unit, Makassar City - Arny Asmoy; Ruliaty, Ruliaty; M.Hidayat (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine and analyze the influence of work motivation on employee performance in the Indonesian Red Cross Blood Transfusion Unit, Makassar City. The type of research used is quantitative descriptive. The population in this study were all employees of the Indonesian Red Cross Blood Transfusion Unit in Makassar City. This research used a saturated sampling technique with a sample size of 95 respondents. The data collection technique uses a questionnaire technique. The data analysis technique used to test the hypothesis is simple linear regression and t-test (partial test) which is processed using statistical calculations via the Statistical Package for the Social Science (SPSS) version 26. The results of the study show that work motivation has a positive and significant effect on employee performance. at the Indonesian Red Cross Blood Transfusion Unit in Makassar City as evidenced by the Work Motivation coefficient (X) value of 0.414 and the calculated t value of 3.859 > t table 1.661 with a significant value of 0.000 < 0.05. So it can be concluded that Work Motivation has a positive and significant effect on Employee Performance At the Indonesian Red Cross Blood Transfusion Unit, Makassar City